Design and the process of developing a digital learning resource on Epilepsy and health guidance - Erichsen, Torunn; Høium, Kari (Nordisk Tidsskrift for Helseforskning, 2021)
Digital learning resources enables new possibilities for teaching and interaction. In this paper we share our experiences with the development of the digital learning resource Epilepsy and Health Counselling, published on OsloMet’s open learning platform in 2018. To ensure clinical relevance, development was conducted in partnership with representatives from the field of practice. This learning resource was developed using the PICA model (presentation, interaction, collaboration, analysis), OsloMet’s instruction for all major holistic teaching materials that are to be published on the University’s public platform. Publishing this resource on an open online platform, free to use, makes it a lot more accessible both for students and employees in the field of practice. This flexibility enables students to use the resource as an integrated part of their practice periods. In conclusion, this paper points to the need for further research on how digital learning resources and technology supported learning can enhance student learning.
Keywords: mooc; epilepsy; patient education; e-learning resource